Resilience, parental stress, and family functioning associated with quality of life: a study with caregivers of children and adolescents with Cerebral Palsy - Sotero, Luciana; Fernandez, Fábio André Ferraz; Bezerra, Patrícia da Silva; Queiroz, Juliana Maciel; Pontes, Fernando Augusto Ramos; Silva, Simone Souza da Costa (Frontiers in Education, 2026)
Cerebral Palsy (CP) is a chronic and non-progressive condition that affects motor and cognitive development, generating various limitations in daily activities and requiring continuous care. The diagnosis can have profound impacts on family dynamics. The quality of life of parents/caregivers may be influenced by multiple factors, such as physical and emotional overload, parental stress, socioeconomic difficulties, among others. Thus, the aim of this study was to investigate the quality of life of parents/caregivers of children and adolescents with CP in Portugal, considering sociodemographic, individual (resilience, parental stress), and family (family functioning) variables. A total of 176 caregivers participated, including 149 mothers and 27 fathers. The following instruments were administered: Sociodemographic Questionnaire, World Health Organization Quality of Life - Bref (WHOQOL-BREF), Resilience Scale (CD-RISC), Parental Stress Index (PSI), and the Systemic Clinical Outcome Routine Evaluation (SCORE-15). The results revealed that medium/high socioeconomic status favored the physical and environmental domains of quality of life, whereas low socioeconomic status was positively associated with social relationships. Lower levels of parental stress, greater resilience, and better family functioning were found to be associated with better quality of life among caregivers of children/adolescents with Cerebral Palsy . The findings reinforce the importance of developing family-centered interventions that promote resilience and reduce parental stress, contributing to the improvement of caregivers’ quality of life.